Membedah Keindahan Uslub Majaz dan Kinayah dalam Hadits (April & October, 2025)
This study examines the beauty and function of majaz and kinayah styles in the texts of the hadiths of the Prophet Muhammad ﷺ through a qualitative approach and content analysis method. The main focus is to understand how the majaz and kinayah styles not only beautify the delivery of the message, but also deepen the moral, spiritual, and ethical meanings contained in the hadiths. The research method used is qualitative with a content analysis approach. Data collection was conducted through literature review using documentation techniques, while data analysis followed the stages of reduction, presentation, and descriptive-qualitative conclusion drawing. The research findings indicate that majaz serves as a symbolic and poetic tool that facilitates the understanding of abstract messages, such as the depiction of Allah's closeness to His servants and the dynamic nature of the heart. Meanwhile, kinayah is used to convey implied meanings through subtle satire or metaphor, reinforcing Islamic teachings such as steadfastness in adhering to the Sunnah and kindness toward women. The use of majaz and kinayah in hadiths demonstrates the linguistic sophistication of the Prophet ﷺ and requires contextual understanding to avoid erroneous literal interpretations. This research makes an important contribution to enriching linguistic and religious understanding, while also serving as a foundation for further scientific studies in the fields of balaghah and hadith studies.